2014
DOI: 10.1136/bcr-2014-204014
|View full text |Cite
|
Sign up to set email alerts
|

A rare cause of dilated bile duct incidentally detected on imaging

Abstract: Adenomas involving the extrahepatic bile ducts are rare benign tumours of the biliary tract. Given the asymptomatic nature of these tumours and the natural progression of biliary adenoma to carcinoma including cholangiocarcinoma, early detection is challenging. We present a case of an octogenarian woman with a remote history of gallstones who initially presented to the gastroenterology office for an incidental finding of biliary dilation, and whose subsequent imagings and biopsy suggested common bile adenoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Three extrahepatic bile duct adenomas were diagnosed at our institution among a total of 10 559 bile duct pinch biopsies and surgical specimens (0.03 %) over 13 years. One of our cases has been reported previously 1 . On extensive review of the literature, we found another 36 cases making a total of 39 cases of extrahepatic biliary adenomas reported to date 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 ( Table1 and Fig.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Three extrahepatic bile duct adenomas were diagnosed at our institution among a total of 10 559 bile duct pinch biopsies and surgical specimens (0.03 %) over 13 years. One of our cases has been reported previously 1 . On extensive review of the literature, we found another 36 cases making a total of 39 cases of extrahepatic biliary adenomas reported to date 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 ( Table1 and Fig.…”
Section: Discussionmentioning
confidence: 80%
“…There is little uniformity in the nomenclature applied to benign epithelial lesions and various classifications have been proposed. According to the WHO classification, they are divided into five different types: tubular, papillary (also known as papillomas), tubulopapillary, biliary cystadenoma, and papillomatosis 1 . Adenomas comprise two-thirds of benign biliary tumors 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Three extrahepatic bile duct adenomas were diagnosed at our institution among a total of 10 559 bile duct pinch biopsies and surgical specimens (0.03 %) over 13 years. One of our cases has been reported previously [1]. On extensive review of the literature, we found another 36 cases making a total of 39 cases of extrahepatic biliary adenomas reported to date [2 -28] (• " Table1 and…”
Section: Casementioning
confidence: 88%
“…One of our cases presented with recurrent bacteremia in the setting of underlying primary sclerosing cholangitis. Two reported cases were asymptomatic with incidental findings of biliary dilation on imaging [1,8]. One case was found incidentally in a surgical resection specimen performed for duodenal adenocarcinoma [11].…”
Section: Demographics and Presentation !mentioning
confidence: 99%
See 1 more Smart Citation